If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying V = F(a + B) Reorder the terms: V = F(B + a) V = (B * F + a * F) V = (BF + aF) Solving V = BF + aF Solving for variable 'V'. Move all terms containing V to the left, all other terms to the right. Simplifying V = BF + aF
| 4t-9-3t-8= | | -5v=-15 | | 325+50x=760 | | -30=10v | | x+=3x-7 | | F(-3)=-7(-3)-4 | | x^3+4x^2+9x+10=0 | | 4x^2-5=-77 | | X-14.1=2.7 | | b=3c | | 1+2u=23+u | | 23-y+2y=34 | | 4-2m=4-6m | | 2x+6y=22 | | 9u-u=40 | | F(4)=-7(4)-4 | | (x+3)+(2x-8)=28 | | 14-0.2(x-10)=0.4(25+x) | | 8v+v=54 | | 36x-3=123 | | 5x-2y+4-x-y= | | 2(6+n)=52 | | 17-6.10*/2+12= | | 164+10=14 | | 15+25=X | | -164+10=14 | | -24-3x=6-8x | | 6=7w-5w | | 17-6.10/2+12= | | 72-3x=24x+24 | | 5y+3y=8 | | 17-6.10*2+12= |